2012
DOI: 10.1145/2377677.2377743
|View full text |Cite
|
Sign up to set email alerts
|

First insights from a mobile honeypot

Abstract: Computer systems are commonly attacked by malicious transport contacts. We present a comparative study that analyzes to what extent those attacks depend on the network access, in particular if an adversary targets specifically on mobile or non-mobile devices. Based on a mobile honeypot that extracts first statistical results, our findings indicate that a few topological domains of the Internet have started to place particular focus on attacking mobile networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…In our previous measurements from January 2012 [4] we found similar results. The most significant difference is the absolute number of attacks on the mobile system and the darknet.…”
Section: Comparison With Previous Measurementssupporting
confidence: 86%
See 2 more Smart Citations
“…In our previous measurements from January 2012 [4] we found similar results. The most significant difference is the absolute number of attacks on the mobile system and the darknet.…”
Section: Comparison With Previous Measurementssupporting
confidence: 86%
“…However, the term "mobile honeypot" is not well-defined and there is only very limited work on the design of a measurement system that allows for both, the analysis of the mobile as well as non-mobile world. In this paper we extend our previous work [4] and make the following core contributions:…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Barron et al operated honeypots deployed in multiple geolocations and analyzed attacks from the perspective of honeypot locations [41]. Another study using honeypots [42] showed that the characteristics of attacks vary depending on the region. The results of Spoki [43], a method for observing Internet scanning activity, showed that different regions have different scanning activity characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…Collapsar can manage a large number of interactive honeypots, e.g., Honeypot farms. The concept of honeypot has been adopted to detect attacks to IoT devices [23,25,29,32] and mobile devices [39]. Our system is working towards Ethereum clients, which have di erent targets with previous systems.…”
Section: Related Workmentioning
confidence: 99%